AN ANALYSIS ON SME DEVELOPMENT MODEL (A STUDY ON THE DEVELOPMENT OF SME) - Hasibuan, Lailan Safina (Jurnal Entrepreneur dan Entrepreneurship, 2018)
This research aims to evaluate SMEs development models done by an institution that have social responsibility. The Bank of Sumatra Utara was chosen for achieving many success in developing SMEs. The result is believed to be useful for the government and the institution to further develop the SMEs. This research reveals the strengths, weaknesses, opportunities and threats that the SMEs face, especially the SMEs that are being developed by the institution. This research uses quantitave descriptive approach with SWOT method. The research began with model identification on SMEs development, marketing, funding and other facilities related to SMEs development under the institution. Further, SWOT matrix was mapped in order to choose the best strategy to develop the SMEs. The result of this research reveals that SMEs development strategy of the Bank of Sumatra Utara is an aggressive strategy, with courses/training in all aspects of enterprise management and establishing relationship with other institutions and universities for knowledge and technology transfer as the models of development.